2011
DOI: 10.1007/s00296-011-1879-x
|View full text |Cite
|
Sign up to set email alerts
|

Levels of lectin pathway proteins in plasma and synovial fluid of rheumatoid arthritis and osteoarthritis

Abstract: The innate immune system contributes to the development of rheumatoid arthritis (RA). A potent contributor to such processes is the complement system. The complement system is known to be activated in the inflammatory phases of osteoarthritis (OA). The lectin pathway of the complement system is activated through the recognition of pathogens or altered self-structures by mannan-binding lectin (MBL) or one of the three ficolins in collaboration with MBL-associated serine proteases (MASPs). We assessed the lectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 22 publications
2
32
1
Order By: Relevance
“…Doherty et al found C3 activation to be associated with RA and gout but not with OA [25]. A recent study looking specifically at the levels of lectin pathway proteins found a significant association of the level of these proteins in plasma and synoial fluid (SF) with RA and OA [26]. Several proteomic studies have identified components of complement system as differentially expressed proteins in synovial fluid [27,28], serum [29] and cartilage [30] samples from OA patients.…”
Section: Innate Immunitymentioning
confidence: 99%
“…Doherty et al found C3 activation to be associated with RA and gout but not with OA [25]. A recent study looking specifically at the levels of lectin pathway proteins found a significant association of the level of these proteins in plasma and synoial fluid (SF) with RA and OA [26]. Several proteomic studies have identified components of complement system as differentially expressed proteins in synovial fluid [27,28], serum [29] and cartilage [30] samples from OA patients.…”
Section: Innate Immunitymentioning
confidence: 99%
“…Among other factors, it is now appreciated that the complement system plays an important role in the pathogenesis of RA. Complement activation is essential for disease progression in passive transfer mouse models of RA, and complement fragments derived from the activation process have been found in the synovium of RA patients (57). Furthermore, complement-directed therapeutics have shown excellent efficacy in mouse models of RA such as collagen antibody-induced arthritis (CAIA) (8, 9).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the terminal pathway components C5, C6, C7, C8 and C9 are secreted, which are able to assemble as MAC [24,65]. For the recognition molecules of the LP there is less evidence of local production by monocytes; however, it was shown that monocytes have intracellular M-ficolin and in synovial fluid of RA patients there was a correlation between M-ficolin and the total number of blood monocytes [42,66]. Several control proteins are also secreted by cultured monocytes, such as FH, FI, C4BP and C1INH [59,62,67].…”
Section: Monocytesmentioning
confidence: 99%